Pengamalan Ibadah Salat Mahasiswa Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan di Lingkungan II Kelurahan Sihitang - Yuli Ramadhayanti; Aida hajijah; Muhammad Ammar Nasution (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The performance of prayer is a fundamental obligation in Islam that must be observed by every Muslim who has reached puberty and possesses sound reasoning. Consistent prayer practice plays an important role in shaping students’ religious attitudes and personal character. This study aims to examine the practice of prayer among students of the State Islamic University of Syekh Ali Hasan Ahmad Addary Padangsidimpuan in Environment II, Sihitang Village, as well as to identify the factors influencing their prayer practices. This research employs a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. In this study, prayer practice is understood as performing prayer correctly in accordance with Islamic teachings, on time, and accompanied by awareness, reverence, and humility. The findings indicate that students’ prayer practices are influenced by several factors, including internal factors such as religious awareness and motivation, external factors related to social interaction, environmental conditions, and family background. These findings suggest that students’ prayer practices are shaped not only by individual religious understanding but also by the surrounding social and environmental contexts.